2011
DOI: 10.1007/s10995-011-0814-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Depressive Symptoms and Social Support in Adolescent Mothers

Abstract: Previous studies have suggested that adolescent mothers with higher social support have lower depressive symptoms. This is a longitudinal study of adolescent mothers to examine the association of social support and depressive symptoms over one year postpartum. This was a prospective study of adolescent mothers (N at baseline = 120, N at 1 year = 89; age \ 19 years) enrolled in a teen tot program. Participants completed the Center for Epidemiological Studies Depression Scale for children (CES-DC) and the Duke-U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 32 publications
10
74
2
2
Order By: Relevance
“…The consensus among researchers is that an increased level of social support is associated with less PPD (Brown et al, 2012;Chien et al, 2012;R. C. Edwards et al, 2012;Shapiro & Fraser, 2013;Xie et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consensus among researchers is that an increased level of social support is associated with less PPD (Brown et al, 2012;Chien et al, 2012;R. C. Edwards et al, 2012;Shapiro & Fraser, 2013;Xie et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Support is paramount, and early recognition and treatment of PPD among disadvantaged populations in particular is an urgent health issue (Kim et al, 2012). Many studies have found that increased levels of support were associated with lower PPD scores (Brown, Harris, Woods, Burman, & Cox, 2012;Chien, Tai, & Yeh, 2012; R. C. Edwards et al, 2012;Fowles et al, 2012;Quelopana, Champion, & ReyesRubilar, 2011). In a longitudinal study of adolescent mothers in the United States (N 5 120 at baseline), Brown et al (2012) examined social support in relation to depressive symptoms over a 1-year postpartum period (N 5 89 at 1 year).…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support [28], specifically that involving the adolescent's mother and partner [14,29], has been linked to depression. This connection has stood up in both cross-sectional [29] and longitudinal research [14,28] and during periods of pregnancy [14,29] postpartum [14], and up to one year after birth [28].…”
Section: Depressionmentioning
confidence: 99%
“…Women have been found to have an almost doubled risk of depression when compared to men (Atkins 2010), and lone mothers are three times more predisposed to poor health and depression than their married counterparts (Cairney et al 2004;Colton et al 2015). Age and race are correlates of this association, with younger women being more predisposed to depression than their older counterparts, (Brown et al 2012;Horwitz et al 2007), and lone mothers of color having a higher risk of depression than white mothers (Wang 2004). The number of children is an important predictor of maternal mental health, with more children corresponding with an increase in risk for depression (Horwitz et al 2007;Sperlich et al 2011b).…”
Section: Prior Research Investigating Lone Motherhood and Depressionmentioning
confidence: 99%